Smartphone Usage on Students Learning English: The Impact of School Policy - BJ Pratiwi; Rini Nuryanti (Hasanuddin University, 2018)
This paper explores the reactions from students and teachers about the potential of using Smartphone on students learning in school. Today’s Smartphone is an important device of a user’s daily life because it has many applications. It can facilitates the users. In learning process, Smartphone can help the teachers and the students. Using Smartphone offers benefits when in learning process particularly in English. It facilitates the students to deliver their works and share information to their classmates through Whatsapp (WA). It can also help students to learn independenly in listening and speaking through English Listening & Speaking Application. Then the students can translate several words by using Dictionary Appilcation. Moreover, it can be stressed that internet in Smartphone can provide them with many resources to find diverse materials that they learned in English. However, using Smartphone has disadvantages and challenges in learning English. It makes students do things instantly. They do not focus to learn more. Furthermore, the students are spending long time for chatting in facebook, twitter, instagram, and other social media, browsing non-academic websites, playing games in the middle of the lesson, and cheating along the tests. In addition, the students can be addicted to use it.